2016
DOI: 10.1016/j.ifacol.2016.12.190
|View full text |Cite
|
Sign up to set email alerts
|

Planning Operator Support in Cyber-Physical Assembly Systems

Abstract: Abstract:Due to the complexity of assembly processes, a high ratio of tasks is still performed by human workers.Short-cyclically changing work contents due to smaller lot sizes, especially in the varied series assembly, increases both the need for information support as well as the risk of rising physical and psychological stress. The use of technical and digital assistance systems can counter these challenges. Through the integration of information and communication technology as well as collaborative assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…This category reviews the main technologies which allow the integration of humans into CPPS. To support humans, CPS need human machine interaction (HMI) methods, as explored in [116,117]. In their works, they describe how HMI methods have evolved from indicator lights, buttons and levers through to every day graphical user interfaces (GUI), keyboards, mouse and touchscreens, before arriving to the concept of multimodal interfaces [118], where the voice, hands, and entire body become a communication channel.…”
Section: Data Analysis: This Cluster Discusses How Informationmentioning
confidence: 99%
“…This category reviews the main technologies which allow the integration of humans into CPPS. To support humans, CPS need human machine interaction (HMI) methods, as explored in [116,117]. In their works, they describe how HMI methods have evolved from indicator lights, buttons and levers through to every day graphical user interfaces (GUI), keyboards, mouse and touchscreens, before arriving to the concept of multimodal interfaces [118], where the voice, hands, and entire body become a communication channel.…”
Section: Data Analysis: This Cluster Discusses How Informationmentioning
confidence: 99%
“…As the initiatives as the digitalization and industry 4.0 will continue to receive much focus, it is important to incorporate the industrial requirements in such initiatives. In such a way, the suggested performance improvements in cyber-physical assembly systems [27] can be achieved.…”
Section: Focus Area #3mentioning
confidence: 99%
“…As researchers suggest that cyberphysical assembly systems can provide improved production performance [27], there are new possibilities of implementing new technology to support operators in manual assembly. Already a decade ago, industry started to implement smart sensors in their production to improve traceability which in earlier research has been suggested to increase the collaborative, flexible and responsive characteristics of manufacturing systems which continuously become more complex every day [28].…”
Section: Manual Assembly and The Digitalization Focusmentioning
confidence: 99%
“…User-centered approaches have been successfully implemented to develop assistance systems in the domains of transportation systems [82], healthcare systems [83], and environmental monitoring systems [84]. Since they employ human factor engineering principles, the acceptance and implementation of the final solution is enhanced [85]. Furthermore, human factors like safety and ergonomic needs are catered for in the early stages of the development process.…”
Section: Figure 5: Model Approaches For Digitalisation [78]mentioning
confidence: 99%
“…The interaction model guides the developer in deriving required user experience with the new technologies. The optimal technologies that fit the derived specification can therefore be selected, tested, and implemented [85].…”
Section: Figure 5: Model Approaches For Digitalisation [78]mentioning
confidence: 99%